Budaya Pluralisme dalam Penerimaan Masyarakat Desa Balun, Kabupaten Lamongan - Fatkhur Rozi; Djarot Meidi Budi Utomo (Universitas Muhammadiyah Sidoarjo, 2019)
Balun Village is an interesting village to this study. The village, called the Pancasila Village, has always instilled the values ​​of pluralism in daily life and well preserved until todays. Now, Pluralism has changed shape into a culture. The SARA issues that still exist in Indonesia there is no ways to give a significant impact and influence in Balun village people's acceptance of the culture of pluralism. The phenomenological approach with in-depth interviews is used to find out the accepted (reception) of the community towards the culture of pluralism. From the results of the study, it can be seen that Balun village community acceptance of pluralism culture is very good. This acceptance is inseparable from the existence of family ties among Balun village communities. But, their perceptions are still based on reason, which can be seen in their perceptions that see pluralism as a virtue and has a lot of benefits to create a harmonious and peaceful in social life.